An Uncommon Occurrence of Three-Fourth Molars Concomitant to Hypodontia in a Nonsyndromic Patient - Schmitd, Ligia Buloto; Assao, Agnes; Ramalho-Ferreira, Gabriel; Faverani, Leonardo Perez [UNESP]; Oliveira, Denise Tostes (Lippincott Williams & Wilkins, 2017)
Bilaterally mandibular and maxillary fourth molars, concomitant to hypodontia, are uncommon. These dental anomalies, called hypohyperdontia, are rare and etiology is not well defined. Several complications may occur as a consequence of supernumerary teeth, such as teeth impaction, resorption of adjacent teeth, and development of cysts and tumors. The authors present an uncommon occurrence of three-fourth molars concomitant to hypodontia and dentigerous cyst associated with impacted mandibular second and third molars in a nonsyndromic patient. The authors attempt to discuss the occurrence of bilaterally fourth molars and reinforce the importance of clinical approach, considering risks and benefits for the patient.
Keywords: Dentigerous cyst; fourth molars; hypohyperdontia; supernumerary teeth